Contribution of self image to interpersonal communication between students in the schools. - Annisa Khairani; Riska Ahmad; Marjohan Marjohan (Journal of Counseling and Educational Technology, 2019)
Millennial generation has low social skills, is less trained in communicating directly and doesn't care about the environment. Good communication skills are needed so that the quality of relationships established with other students becomes better. There are several factors that affect students' ability to interpersonal communication, one of which is self-image. Therefore researchers conducted related research; 1) a picture of self-image and interpersonal communication between students in school and 2) examine the contribution of self-image to interpersonal communication. This research uses a quantitative approach with descriptive methods, then use simple linear regression analysis . Population at SMPN 1 Banuhampu as many as 812 students, with a sample of 282 ofthe self-selected engineering Proportional Random Sampling . The instrument used was a Likert scale , which is about self-image and interpersonal communication . Research findings show that; 1) students' self-image and interpersonal communication generally in the good category, 2) there is a contribution of self-image to students' interpersonal communication of 27.4 % (R = 0. 523 ), significance of 0.000 . This research has implications as a basis Counselor to help students to have good abilities in interpersonal communication.  Millennial generation has low social skills, is less trained in communicating directly and doesn't care about the environment. Good communication skills are needed so that the quality of relationships established with other students becomes better. There are several factors that affect students' ability to interpersonal communication, one of which is self-image. Therefore researchers conducted related research; 1) a picture of self-image and interpersonal communication between students in school and 2) examine the contribution of self-image to interpersonal communication. This research uses a quantitative approach with descriptive methods, then use simple linear regression analysis . Population at SMPN 1 Banuhampu as many as 812 students, with a sample of 282 ofthe self-selected engineering Proportional Random Sampling . The instrument used was a Likert scale , which is about self-image and interpersonal communication . Research findings show that; 1) students' self-image and interpersonal communication generally in the good category, 2) there is a contribution of self-image to students' interpersonal communication of 27.4 % (R = 0. 523 ), significance of 0.000 . This research has implications as a basis Counselor to help students to have good abilities in interpersonal communication.